Somali refugees in urban neighborhoods: an eco-social study of mental health and wellbeing - Ermansons, Guntars; Kienzler, Hanna; Schofield, Peter (Frontiers in Psychiatry, 2024)
Background Impact of pre-migration trauma and post-migration settlement on refugee mental health and wellbeing is well-documented. However, little research has focused on the specific places where refugees settle and spend their daily lives within the post-migration context. This study adopts an eco-social perspective to explore the relationship between urban neighborhoods and refugee mental health and wellbeing. Methods We conducted twenty-six qualitative interviews with Somali refugees in London and Bristol in the UK. The transcripts were coded using an inductive approach and analyzed through thematic analysis. Results Somali refugees navigate a complex urban environment comprising various neighborhood features which include important places near home, interactions with neighbors, and community spaces. While these features afford them resources to improve mental health and wellbeing, they also present challenges such as high urban density, exposure to violence or discrimination, and neighborhood disorder. Conclusion The societal and physical features of urban neighborhoods intersect with refugee experiences of adversity, trauma and stress over time. As eco-social niches, urban neighborhoods are both accommodating, safe and familiar, as well as alien, threatening and unwelcoming. To support mental health and wellbeing and ensure successful settlement, it is essential to recognize the agency of refugees and provide continuous support throughout the entire asylum process and after, ensuring stable and safe living conditions.